Could Changing the DNA Methylation Landscape Promote the Destruction of Epstein-Barr Virus-Associated Cancers? - Sinclair, Alison J. (Frontiers in Cellular and Infection Microbiology, 2021)
DNA methylation at CpG motifs provides an epigenetic route to regulate gene expression. In general, an inverse correlation between DNA hypermethylation at CpG motifs and gene expression is observed. Epstein Barr-virus (EBV) infects people and the EBV genome resides in the nucleus where either its replication cycle initiates or it enters a long-term latency state where the viral genome becomes hypermethylated at CpG motifs. Viral gene expression shows a largely inverse correlation with DNA hypermethylation. DNA methylation occurs through the action of DNA methyl transferase enzymes: writer DNA methyl transferases add methyl groups to specific regions of unmethylated DNA; maintenance DNA methyl transferases reproduce the pattern of DNA methylation during genome replication. The impact of DNA methylation is achieved through the association of various proteins specifically with methylated DNA and their influence on gene regulation. DNA methylation can be changed through altering DNA methyl transferase activity or through the action of enzymes that further modify methylated CpG motifs. Azacytidine prodrugs that are incorporated into CpG motifs during DNA replication are recognized by DNA methyl transferases and block their function resulting in hypomethylation of DNA. EBV-associated cancers have hypermethylated viral genomes and many carcinomas also have highly hypermethylated cellular genomes. Decitabine, a member of the azacytidine prodrug family, reactivates viral gene expression and promotes the recognition of lymphoma cells by virus-specific cytotoxic T-cells. For EBV-associated cancers, the impact of decitabine on the cellular genome and the prospect of combining decitabine with other therapeutic approaches is currently unknown but exciting.